Religious Intolerance: Way to Eliminate Religious Extremism in The Light of Islam and Gandhian Approach - Hussain, Syed Fahad (South Asian Journal of Social Sciences and Humanities, 2022)
India is the largest democracy globally; however, right-wing populism has led to a dramatic  shift in India's political landscape, particularly for religious minorities and Dalits.  Discrimination, abusive slurs, or news of violence against people in this group should not be  tolerated even for a single day. "Hindutva" ideology, or "Hindu nationalism," advocates  violence against Muslims and views them as outsiders and potential threats to the country's  security. That has created a sense of feeling unsafe for Muslims in their own country and an  unending wave of intolerance spread by the progenies of the RSS. In light of the Holy Quran  and Gandhian approach, this paper defines the type of religious intolerance and how it is  spreading and damaging the social fabric of the society and suggests ways to combat religious  intolerance.
Keywords: Hindutva; Intolerance; Populism; Democracy; Gandhian Approach; RSS